Sistem Pengendalian Gerak Sendok Menggunakan Sensor Mpu6050 Dan Metode Pid Berbasis Arduino - Ahmad Fahmi AdamSyah; Hurriyatul Fitriyah; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Difficulty eating is a condition in which a person is unable to eat normally or comfortably. Researchers want to propose a spoon system that can be controlled its stability. The system of this research is the movement of the spoon to be read using the MPU6050 sensor. The value obtained from the sensor will be forwarded to the Arduino Nano processing unit for calculations using the PID controller method where the Kp, Ki, and Kd variables are searched using the trial and error tuning method. The results of these calculations will be used as a spoon mover. Based on the tests that have been carried out, there are conclusions on the test results, first on testing the accuracy of the sensor angle, it can be seen that from 7 experiments from an angle of 0 ° to 180 ° with a multiple of 30 ° on both axes, namely pitch and roll, the percentage error is 0. 59% or less than 1%. The second test of the accuracy of the servo angle based on the setpoint is done, it can be seen that from 7 experiments from an angle of 0 ° to 180 ° with a multiple of 30 ° on both axes, namely roll and pitch, the percentage error is 0.8. Finally, the system speed test has reached stable or commonly called the settling time that has been carried out, it can be seen that from 10 experiments, the initial speed of the system reaches the settling time, which is the average time of both axes, namely 0.99 seconds or under 1 second.